Pengaruh Entertainment, Irritating dan Informativeness Iklan di Website di Kalangan Mahasiswa - Supriyadi, Edy; Putriana, Lies (Journal the Winners: Economics, Business, Management, and Information System Journal, 2010)
There are several advantages and disadvantages and advertising via the Internet. The appeal of advertising may also arise from given information element, the element of comfort but also sometimes lead to disturbing or irritation elements. The limited number of Internet users in Indonesia and the different backgrounds of individual Internet users in Indonesia certainly provide a different assessment of the advertisements contained on the Internet. There are 3 factors which was the starting point to explain how consumers interpret the value of advertising, namely: informativeness, entertainment and irritation. This research aims to discover whether there is a relationship between entertainment, informativeness, and irritation toward advertising values and whether there is a relationship between entertainment and advertising values toward attitude towards web advertising using statistics tools of path analysis and multiple regression. The research shows that there is a significant relationship between independent variables such as informativeness, entertainment and irritation simultaneously toward the advertising value but there are no significant relationship between entertainment and informativeness toward the advertising value individually.Â  In the other model there is a significant relationship between informativeness, irritation and advertising values with the attitude towards web advertising.